2017
DOI: 10.1242/dev.134866
|View full text |Cite
|
Sign up to set email alerts
|

Human haematopoietic stem cell development: from the embryo to the dish

Abstract: Haematopoietic stem cells (HSCs) emerge during embryogenesis and give rise to the adult haematopoietic system. Understanding how early haematopoietic development occurs is of fundamental importance for basic biology and medical sciences, but our knowledge is still limited compared with what we know of adult HSCs and their microenvironment. This is particularly true for human haematopoiesis, and is reflected in our current inability to recapitulate the development of HSCs from pluripotent stem cells in vitro. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
233
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(254 citation statements)
references
References 189 publications
(266 reference statements)
6
233
0
1
Order By: Relevance
“…LMOs proteins, do not present DNA binding domain and rather act through binding of 393 other proteins. This class of protein has not been extensively exploited in programming 394 approaches as much as other transcription factors (Ivanovs et al, 2017). Overexpression 395 of IDs or LMOs could not only provide an alternative approach for programming gene 396 cocktails, but it could also be employed to maintain the progenitor state in culture and 397 prevent their differentiation.…”
Section: Identification Of Membrane Markers Of Lineage Primed Progenimentioning
confidence: 99%
“…LMOs proteins, do not present DNA binding domain and rather act through binding of 393 other proteins. This class of protein has not been extensively exploited in programming 394 approaches as much as other transcription factors (Ivanovs et al, 2017). Overexpression 395 of IDs or LMOs could not only provide an alternative approach for programming gene 396 cocktails, but it could also be employed to maintain the progenitor state in culture and 397 prevent their differentiation.…”
Section: Identification Of Membrane Markers Of Lineage Primed Progenimentioning
confidence: 99%
“…Previous studies have shown that human induced pluripotent stem cells (hiPSCs) can be induced to form hemogenic endothelium (HE), identified as CD144+CD34+ and CD73‐, which could be further differentiated into CD43+ hematopoietic progenitors (HPCs) and then to erythro‐myeloid progenitors (EMPs); these are reminiscent of EMPs in the yolk sac during embryonic hematopoiesis. The differentiation process is MYB‐independent and associated with HOXA expression (Buchrieser, James, & Moore, 2017; Dou et al., 2016; Ivanovs et al., 2017; Ng et al., 2016; Vanhee et al., 2015), indicating this recapitulates primitive hematopoiesis in vivo. Other studies found that hiPSC‐derived macrophages (iPSDMs) could acquire tissue‐specific characteristics in vitro (Takata et al., 2017) and in vivo (Happle et al., 2018; Takata et al., 2017) by coculture with other tissue‐resident cell types.…”
Section: Introductionmentioning
confidence: 99%
“…In the developing mammalian embryo, blood is produced in consecutive waves [7][8][9] . The first wave of hematopoietic progenitors, dubbed "primitive", occurs in the yolk sac blood islands 10 .…”
mentioning
confidence: 99%